Leader Mindfulness as a Buffer in Family Business: Exploring the Effects of Work Stress and Pay Satisfaction on Turnover Intention through Organizational Commitment - Putra, Agung Dwi; Eugene Lambey, Sylvia; Supriyadi Muri, Subur; Maharani, Anita (Universitas Muhammadiyah Pontianak, 2026)
This study examines turnover intention in family businesses by analyzing the effects of work stress and pay satisfaction, with organizational commitment as a mediator and perceived leader mindfulness as a moderator. Using a quantitative survey and PLS-SEM, data were collected from 238 employees working in family businesses. The results show that work stress significantly reduces organizational commitment, while organizational commitment significantly lowers turnover intention and mediates the effect of work stress. Pay satisfaction and perceived leader mindfulness do not significantly affect turnover intention. These findings highlight the importance of strengthening employees’ emotional attachment to improve retention in family business settings. Keywords: Family Business; Turnover Intention; Perceived Leader Mindfulness; Organizational Commitment; Pay Satisfaction